“Today We Act, Tomorrow We Vote”: Latino Religions, Politics, and Activism in Contemporary U.S. Civil Society - Espinosa, Gastón (The annals of the American Academy of Political and Social Science, 2007)
The findings in this study indicate that Catholic and Protestant leaders like Cardinal Roger Mahony of the Archdiocese of Los Angeles and Rev. Samuel Rodríguez of the National Hispanic Christian Leadership Conference drew on religious rhetoric, symbols, moral authority, interfaith religious coalition building, and the Bible in the 2005-2007 immigration reform debate and in their struggle for greater tolerance and inclusion of Latinos in U.S. civil society. Mahony and other Catholics also drew on Catholic social teaching and several strategies employed by César Chávez in their struggles for social justice.